Lack of inhibitory effect of wood creosote on cytochrome P450‐mediated drug metabolism. Issue 1 (15th November 2021) - Chokki, Hirokazu; Nishimura, Yuki; Iwase, Mariko; Kurata, Norimitsu; Shinya, Koichiro; Tsuji, Mayumi; Ito, Masafumi; Asai, Mutsumi; Morino, Hirofumi; Miura, Takanori; Shibata, Takashi; Kiuchi, Yuji
ABSTRACT: Aim: Wood creosote (WC), an over‐the‐counter (OTC) drug, has been used as an anti‐diarrheal agent for many years; however, its safety in combination with other drugs has not been adequately investigated. The current study was conducted to evaluate whether WC may cause drug interactions through the inhibition of cytochrome P450 (CYP). Methods: The inhibitory effects of WC on ethoxyresorufin O‐deethylation, paclitaxel 6α‐hydroxylation, S‐warfarin 7‐hydroxylation, S‐mephenytoin 4′‐hydroxylation, bufuralol1′‐hydroxylation, and midazolam (MDZ) 1′‐hydroxylation were investigated using human liver microsomes as the marker activities for CYP1A2, CYP2C8, CYP2C9, CYP2C19, CYP2D6, and CYP3A4, respectively. In addition, the effects of single and three‐day multiple treatments of WC (30 mg/kg) on CYP2C‐mediated tolbutamide (TB, 20 mg/kg) and CYP3A‐mediated MDZ (15 mg/kg) metabolism were investigated in rats in vivo . Results: WC at clinical doses did not show a considerable inhibitory effect on any of the CYP activities examined in the in vitro study. CYP2C9 and CYP2C19 activities were inhibited by high concentrations of the WC (100 μg/mL); however, the IC50 values were approximately 70 times higher than the reported circulating levels of the main ingredients in WC. Furthermore, there were no marked changes in the pharmacokinetic parameters of TB and MDZ (area under the serum concentration–time curve, maximum serum concentrations, and elimination half‐life) after single or three‐day multiple treatments with WC. Conclusion: These results suggest that clinical doses of WC are unlikely to cause drug interactions mediated by the inhibition of CYPs.